Complications from Needle Thoracostomy: Penetration of the Myocardium. (20th April 2021) - Thomas, Arielle; Wilkinson, K. Hope; Young, Kevin; Lenz, Timothy; Theobald, Jillian
Abstract: We report a rare but serious complication of needle thoracostomy, penetration of the myocardium. Needle thoracostomy is typically performed in the prehospital setting or upon arrival in the emergency department for suspected tension pneumothorax. Needle decompression is generally taught and done anteriorly, in the 2 nd intercostal space on the midclavicular line (MCL). An alternative approach is laterally, along the anterior axillary line (AAL) in the 4 th intercostal space. Our case supports prior literature that the anterior MCL location has a low rate of efficacy to decompress the chest, as well as a high rate of complications. We recommend performing needle decompression laterally at the AAL whether in the field or in the emergency department.